Managing the Emotional Intensities of Gifted Students with Mindfulness Practices - Dorothy Sisk (MDPI AG, 2021)
The emotional intensities of gifted students affect not only their learning, but also the way they live and see the world. This article examines the Theory of Positive Disintegration of Dabrowski to explore the inner world of the gifted. The five levels of development and five overexcitabilities of Dabrowski represent an abundance of physical, sensual, creative, intellectual, and emotional energy that cause inner turmoil but can result in creative endeavors. The benefits of mindfulness practices to meeting the emotional needs of gifted students are presented with examples of deep listening, gratitude, and storytelling as mindfulness practices. A culminating activity of storytelling illustrates the integration of deep listening and gratitude and its effect on the sense of identity of gifted students.